33 Cardiac MRI thresholds for improvement in pulmonary arterial hypertension. (28th January 2023) - Alabed, Samer; Garg, Pankaj; Alandejani, Faisal; Dwivedi, Krit; Maiter, Ahmed; Karunasaagarar, Kavita; Rajaram, Smitha; Hill, Catherine; Thomas, Steven; Gossling, Rebecca; Sharkey, Michael; Wild, Jim M; et al.
Abstract : Introduction: Cardiac MRI (CMR) is the gold standard technique to assess bi-ventricular volumes and function and is increasingly being considered as an end-point in clinical studies. Currently, with the exception of right ventricle (RV) stroke volume, there are no minimally important differences (MIDs) reported for CMR metrics in pulmonary arterial hypertension (PAH). Our study aimed to identify MIDs for CMR metrics that reflect how a patient feels and functions. Materials and Methods: Consecutive treatment-naive patients with PAH between 2010 and 2021 who had two CMR scans (at baseline and at 12 months following treatment) were identified from the ASPIRE registry. The MID in CMR metrics was determined using an anchor-based method combining how a patient "feels" (emPHasis-10 questionnaire) and "functions" (incremental shuttle walking test). RV ejection fraction (RVEF) and RV and left ventricle (LV) end-diastolic volume, RV end-systolic volume and LV stroke volume were measured at baseline and follow-up. Improvement was defined as an increase of at least 47.5m in walking distance and/or decrease of at least 6 points in emPHasis-10 score. Results: 114 patients were included. The MIDs (P<0.05), for metrics for how a patient "feels and functions" for improvement, were an absolute increase in RVEF of 3%, a 10 ml reduction in RVESV or RVEDV and a 5 ml increase in LVSV or LVEDV. Conclusion: This study establishes clinically relevant CMR MIDs for how a patient feels and functions in response to PAH treatment. These findings provide further support for the use of CMR as a clinically relevant surrogate end-point and will aid trial-size calculations for studies using CMR.